2018
DOI: 10.3390/ijerph15102226
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Type D Personality and Depression, Alone and in Combination, on Medication Non-Adherence Following Percutaneous Coronary Intervention

Abstract: Background: Medication adherence after percutaneous coronary intervention (PCI) is essential to preventing the risk of restenosis. Even though Type D personality and depression have been known to affect medication non-adherence, their combined influence on PCI patients remains unclear. Aim: We aimed to identify how both Type D personality and depression were associated with medication non-adherence for 3 months after successful PCI. Methods: This prospective cohort study included 257 PCI patients, who took 3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
3
7
0
1
Order By: Relevance
“…Previous evidence also corroborates this study’s findings that depression is associated with lower medication adherence [45,46,50] with one study reporting that patients were four times more likely to be non-adherent if they reported having depression. [50] Furthermore, prior studies have shown depression increased as ACE scores increased, in addition to those with childhood traumas having more physical symptoms and engaging in more health-risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…Previous evidence also corroborates this study’s findings that depression is associated with lower medication adherence [45,46,50] with one study reporting that patients were four times more likely to be non-adherent if they reported having depression. [50] Furthermore, prior studies have shown depression increased as ACE scores increased, in addition to those with childhood traumas having more physical symptoms and engaging in more health-risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…A deeper study of the issue has contributed to the creation of a type D personality that describes the body's response to distress (Mols and Denollet, 2010 ; Kupper and Denollet, 2018 ; Spek et al, 2018 ). Type D personality is characterized by a high level of negative affectivity and a high level of social inhibition (Sher, 2005 ; Kasai et al, 2013 ; Li et al, 2016 ; Jandackova et al, 2017 ; Borkoles et al, 2018 ; Son et al, 2018 ). The synergy of both variables, according to Mols and Denollet ( 2010 ), is a risk factor with which various other health complications are associated.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been a risk factor for the development and progression of CAD, and a significant relative risk exists (1.5-2.5) ( 7 ). Furthermore, patients with persistent depression after the onset of ACS were found to have lower rates of adherence to quitting smoking, using medications, exercising, and attending cardiac rehabilitation than those without depression ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%